Short-term outcomes of transanal total mesorectal excision combined with modified Bacon’s procedure for treating low rectal cancer: an analysis of 30 cases - Fu Zhiyong; Fan Yushi; Guo Qing; Yang Xuanhua; Zhou Dongbing; Teng Qing; Huang Haixia; Zhu Yongfei; Jing Rong; Ren Mingyang (结直肠肛门外科)
[Objectives] To analyze the short-term outcomes of transanal total mesorectal excision (taTME) combined with modified Bacon’s procedure for treating low rectal cancer. [Methods] This was a retrospective analysis of 74 patients with low rectal cancer treated with taTME at the Nanchong Central Hospital—the Affiliated Hospital of North Sichuan Medical College between March 2020 and August 2021. Patients were divided into the treatment group (n=30, received taTME combined with modified Bacon’s procedure) and the control group (n=44, received taTME and one-stage anastomosis). The followings were compared between the two groups: postoperative complications, operation time, intraoperative blood loss, distance between the anastomotic site and the anal margin, intraoperative complications, prophylactic stoma, conversion to laparotomy, circumferential resection margin positive rate, proximal resection margin positive rate, distal resection margin positive rate, membrane integrity, and lymph node yield. [Results] All surgeries were uneventful, and no case were converted to open operation. There were no severe intraoperative complications. The median distance between the anastomotic site and the anal margin was 0 mm for the treatment group and 22.5(10.0, 30.0) mm for the control group. Five patients in the control group and none in the treatment group had prophylactic stoma. The two groups did not differ significantly in operation time, intraoperative blood loss, and prophylactic stoma rate(P>0.05). All circumferential, proximal, and distal resection margins were negative, and membrane integrity was maintained in all cases. Median lymph node yield was 13.5(6.8, 20.3) for the treatment group and 16.0(11.3, 22.5) for the control group, with no significant between-group difference (P>0.05). There was no occurrence of postoperative anastomotic bleeding and anastomotic stenosis for both groups, and no occurrence of intestinal canal retraction or necrosis for the treatment group. The overall incidence of complications was significantly lower in the treatment group than in the control group (P<0.05). The two groups were similar concerning the incidence of anastomosis-related complications (P>0.05). [Conclusion] taTME combined with modified Bacon’s procedure has lower overall complications rate than taTME and one-stage anastomosis. The two procedures were comparable in terms of operation time, intraoperative blood loss, and pathology findings, and they were both considered safe and feasible.